Identity as a catalyst for success - Bennett, Dawn (International Society for Music Education, 2008)
Success as a musician is most commonly assumed to be the attainment of a performance career; however, careers solely in performance are rare, often short-lived, and not desirable to everyone. This paper is drawn from a study which explored the perception of the musician as a performer, and which sought to find out whether practising musicians would support redefining their profession to encompass those working within non-performance roles. It presents the results of two focus groups held with musicians working in performance and non-performance roles. The musicians were asked: ?What is a musician?? The ensuing debate encompassed notions of success, career expectations, performance careers, and the importance of intrinsic career satisfaction. Participants suggested that musicians? careers continually evolve according to available opportunities and both professional and personal needs. The definition of the musician as a performer was found to lack specificity and to suggest an unrealistic perception of the profession of music. The results of this study support the argument that the term musician needs to be redefined; that redefinition has support within the profession; and that music educators have a crucial role to play in encouraging students to consider what kinds of musician they would like to be.